2020
DOI: 10.1021/acs.jced.9b01082
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid Equilibria of the CH4 + CO2 + H2S Ternary System with Two Different Global Compositions: Experiments and Modeling

Abstract: The vapor-liquid equilibrium for two mixtures containing methane, carbon dioxide and hydrogen sulphide was determined experimentally by a static-analytic method. Thirty-one data points were acquired for a range of temperatures from 243 K to 333 K at pressures up to 11 MPa. The measured data were correlated with the Peng Robinson equation of state (EoS) and different mixing rules, which led to the conclusion that a cubic EoS could simultaneously predict the existence of a 3-phase region and 2 critical points on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Natural gas will play a key role in hydrogen production [3]. These advantages make natural gas a promising candidate to replace liquid fossil fuels and coal, and to be a transition fuel until renewable energy sources are feasible on a large scale [4,5]. It is well known that about 40% of the remaining natural gas sources have a CO 2 concentration higher than 2% and a H 2 S concentration higher than 100 ppm [6].…”
Section: Introductionmentioning
confidence: 99%
“…Natural gas will play a key role in hydrogen production [3]. These advantages make natural gas a promising candidate to replace liquid fossil fuels and coal, and to be a transition fuel until renewable energy sources are feasible on a large scale [4,5]. It is well known that about 40% of the remaining natural gas sources have a CO 2 concentration higher than 2% and a H 2 S concentration higher than 100 ppm [6].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [20] conducted a phase simulation study of the coexistence systems of natural gas and water containing CO 2 and H 2 S, and conducted the sensitivity analysis of pressure, temperature, water content, and other factors. In the experiment of CO 2 -H 2 S coexistence systems, Theveneau [21] and Souza [22], have conducted phase equilibrium experiment of CO 2 -H 2 S-CH 4 system. Zhang [23] conducted a phase equilibrium experiment of CO 2 -H 2 S-crude oil system.…”
Section: Review On the Mechanism Of Co 2 Storage And Enhanced Gas Rec...mentioning
confidence: 99%
“…A few studies of the phase equilibria of the (CO 2 + CH 4 + H 2 S) ternary system have been reported [3,4,[42][43][44], although none of these address the high dilution behavior of H 2 S and so only limited comparisons are possible. Hensel et al [4]…”
Section: H 2 S Partition Coefficientsmentioning
confidence: 99%
“…Phase compositions were not analyzed. Recently, Theveneau et al[44] reported VLE measurements with full composition analysis for two different global compositions at temperatures between (243.50 and 333.13) K and pressures up to 11.24 MPa. However, in their study, x 3 varied between 0.427 and 0.986 and so comparisons are not meaningful.…”
mentioning
confidence: 99%